The riverscape and the river - Haslam, S. M. (Sylvia Mary), 1934- (Cambridge University Press, 2008)
In this study Dr Haslam examines how the quantity, function and ecology of water changes as it moves from watershed to river. The development of river and riverscape, their ecology, the effect of human activities (such as water abstractions, flood control and management for recreational use) and water resources are described both in principle and using case histories. Contrasting examples are given from across the world, including Iceland, Hungary, Malta, Britain and the USA, which enables understanding of how water and riverscape interact with each other, and with human impact. The study, development and loss of water resources is also described, including the extreme example of Malta, whose clean water now depends solely on oil imports. This innovative book is written for graduate students and professionals interested in how water and riverscape interact.